12. ASSESSMENT OF SEXUAL HEALTH OF PATIENTS WHO HAD TOTAL HYSTERECTOMY FOR EARLY STAGE CERVICAL CANCER AT THE DEPARTMENT OF GYNECOLOGY AND SURGERY, NATIONAL CANCER HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current state of sexual health of patients after 3 months of total hysterectomy for early-stage cervical cancer in patients at the Gynecology Surgery Department – National Cancer Hospital.Subjects and Methods: A cross-sectional descriptive study was conducted on 43 cervical cancer patients who underwent total hysterectomy at the Gynecology Surgery Department of National Cancer Hospital in 2024. The Female Sexual Function Index (FSFI) was used for assessment.Results: After surgery, the frequency and quality of sexual intercourse decreased compared to before the surgery. The average frequency in the past 4 weeks dropped from 5.7 times to 3.4 times. Evaluations of quality, such as libido, arousal, and satisfaction, all decreased, while difficulty with lubrication and pain during intercourse increased. All of these changes were statistically significant.Conclusion: All aspects of sexual health assessed in patients showed a decline after surgery. These results are significant for the care, counseling, and guidance of patients, helping them to better adapt to their new life.
Keywords: sexual health; cervical cancer; surgery